Safety, tolerability, pharmacodynamic and wellbeing effects of SPL026 (dimethyltryptamine fumarate) in healthy participants: a randomized, placebo-controlled phase 1 trial - James, Ellen; Erritzoe, David; Benway, Tiffanie; Joel, Zelah; Timmermann, Christopher; Good, Meghan; Agnorelli, Claudio; Weiss, Brandon M.; Barba, Tommaso; Campbell, Graham; Baker Jones, Michelle; Hughes, Charlotte; et al. (Frontiers in Psychiatry, 2024)
Background: Due to their potential impact on mood and wellbeing there has been increasing interest in the potential of serotonergic psychedelics such as N,N-dimethyltryptamine (DMT) in the treatment of major depressive disorder (MDD).The aim of Part A of this study was to evaluate safety, tolerability, pharmacokinetics (PK) and pharmacodynamic (PD) profile of escalating doses of SPL026 (DMT fumarate) in psychedelic-naïve healthy participants to determine a dose for administration to patients with MDD in the subsequent Phase 2a part of the trial (Part B).Methods: In the Phase 1, randomized, double-blind, placebo-controlled, parallel-group, single doseescalation trial, psychedelic-naïve participants were randomized to placebo (n=8) or four different escalating doses (9, 12, 17 and 21.5 mg intravenously [IV]) of SPL026 (n=6 for each dose) together with two-to-one psychological support. PK and acute (immediately following dosing) psychometric measures (including Mystical Experience Questionnaire [MEQ], Ego Dissolution Inventory [EDI], and intensity rating visual analogue scale [IRVAS]) were determined. Additional endpoints were measured as longer-term change from baseline to Days 8, 15, 30 and 90. These measures included the Warwick and Edinburgh Mental Wellbeing Scale and Spielberger's State-Trait Anxiety Inventory.Results: SPL026 was well tolerated, with an acceptable safety profile, with no serious adverse events. There was some evidence of a correlation between maximum plasma concentration and increased IRVAS, MEQ, and EDI scores. These trends are likely to require confirmation in a larger sample size. Using the analysis of the safety, tolerability, PD, PK results, doses of 21.5 mg SPL026 were the most likely to provide an intense, tolerated experience.Based on the data obtained from the Phase 1 part of this trial, a dose of 21.5 mg SPL026 given as a 2-phase IV infusion over 10 min (6 mg/5 min and 15.5 mg/5 min) was selected as the dose to be taken into Part B.